Traces et sens de l'Histoire chez les voyageuses françaises et britanniques dans l'Italie préunitaire (1815-1861) - Nicolas Bourguinat (Genre & Histoire)
Historical Traces and Historical Perceptions in French and British Women’s Travel Writings on Preunified Italy (1814-1861).This article deals with women's travel writing about Italy in the first half of the nineteenth century (1814-1861), using an extensive definition of travel literature. The analysis draws on more than 150 references written and/or published by French and British women: travel books, travel diaries, extracts from autobiographies or memoirs, private letters.  Rather than limiting the study to a few “representative” women, I describe a more general feminine view of Italy as a land of classical culture and of seductive leisure, but also as a foreign and dominated country whose destiny was affected by the accidents of History. Visiting post-Napoleonic Italy, French and especially British women did not limit their perceptions and feelings to the usual stereotypes about Italian ways of life and the domestic sphere. As they traveled, discovering the cities and the people, they also discuss in their writings matters connected with politics and history; for example, the legacy of the French occupation of Italy before 1814, or the signs of backwardness and the authoritarianism of political life in the Papal States and other principalities. These women travellers also stress the possibilities for the country’s regeneration, especially for the generation of women travellers who visited Italy after the 1848 revolutions.